Nocturnal Behaviour of Adult Peregrines at the Nest during Nestling Period - Rejt, L. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
В 2000 и 2002 гг. проведены исследования, целью которых было изучение ночной гнездовой активности сапсанов в Варшаве. Благодаря камерам наблюдения возможно было отслеживать поведение взрослых особей и установить время, которое они проводят с птенцами. Материал собран между 20:00 и 4:00 часами в течение 34 ночей в 2000 г. и 24 — в 2002 г. Установлено, что в начале гнездового периода самка почти непрерывно находится рядом с птенцами. Далее это время уменьшается и достигает всего нескольких минут за ночь. Время пребывания самца в гнезде не превышало нескольких минут за ночь в течение всего сезона. In 2000 and 2002, the same pair of Peregrine Falcons occupied a nest box situated on the highest building within the city centre. The nest box was monitored with a video camera and an infrared lamp. Records collected between 20:00 and 4:00 (DST) during the nestling stage (after the first chick hatching to fledging the last one) were used for analysis. Data from 34 nights in 2000 and 21 nights in 2002 were analysed. The average share of female was about 50% but time spent by the adults within the nest changed as the breeding season progressed. Late in the season parents spent only several minutes on nest.